Implications of High Levels of Activin B in Human Keloid: A Case Report - Ham, Seungmin; Harrison, Craig; Temple-Smith, Peter; Southwick, Graeme (Archives of Clinical and Medical Case Reports, 2022)
Abstract not available in the source database.